Control of Pseudomonas mastitis on a large dairy farm by using slightly acidic electrolyzed water. (18th May 2017) - Kawai, Kazuhiro; Shinozuka, Yasunori; Uchida, Ikuo; Hirose, Kazuhiko; Mitamura, Takashi; Watanabe, Aiko; Kuruhara, Kana; Yuasa, Reiko; Sato, Reiichiro; Onda, Ken; Nagahata, Hajime
Abstract: The disinfection effect of slightly acidic electrolyzed water (SAEW) use in a farm where Pseudomonas mastitis has spread was evaluated. Despite the application of antibiotic therapy and complete cessation of milking infected quarters, numerous new and recurrent Pseudomonas aeruginosa clinical mastitis infections (5.8–7.1% of clinical mastitis cases) occurred on the farm from 2003 to 2005. Procedural changes and equipment modifications did not improve environmental contamination or the incidence of Pseudomonas mastitis. To more thoroughly decontaminate the milking parlor, an SAEW system was installed in 2006. All milking equipment and the parlor environment were sterilized with SAEW (pH 5–6.5, available chlorine 12 parts per million) before and during milking time. After adopting the SAEW system, the incidence of clinical and subclinical Pseudomonas mastitis cases decreased significantly ( P  <   0.0001) and disappeared. These findings suggest that SAEW effectively reduced the incidence of mastitis in a herd contaminated by Pseudomonas species. This is the first report to demonstrate the effectiveness of disinfection by SAEW against mastitis pathogens in the environment.